Influence of different zirconia surface treatments on biofilm formation in vitro and in situ. Issue 4 (13th February 2022) - Jaeggi, Marco; Gyr, Sharon; Astasov‐Frauenhoffer, Monika; Zitzmann, Nicola U.; Fischer, Jens; Rohr, Nadja
Abstract: Objectives: To determine whether the surface treatment of zirconia affects biofilm formation in an in vitro three‐species biofilm model and in situ. Material and methods: Zirconia surfaces considered for the transmucosal portion of a zirconia implant were compared with polished pure titanium grade 4 (Tp). Disks 13 mm in diameter of either polished (Zp), polished and heat‐treated (Zpt), machined (Zm), machined and heat‐treated (Zmt) and sandblasted, etched and heat‐treated (Z14) zirconia were fabricated. Surface roughness and wettability of specimens was measured. Biofilm formation was evaluated by safranin staining and scanning electron microscopy (SEM) using a three‐species model, and intraorally with 16 volunteers carrying oral splints in two independent experiments. Relative biofilm formation was compared with Kruskal–Wallis followed by Bonferroni post hoc test (α = 0.05). Results: In vitro biofilm formation with optical density values on Zp (0.14 ± 0.01), Zpt (0.14 ± 0.02), Zm (0.13 ± 0.01) and Zmt (0.13 ± 0.01) was significantly lower than on Tp (0.21 ± 0.05) and Z14 (0.20 ± 0.04) ( p  < .05). In situ biofilm formation was significantly higher on Z14 (0.56 ± 0.45) ( p  < .05), while no significant differences in optical density were observed among Zp (0.25 ± 0.20), Zm (0.36 ± 0.34) and Tp (0.28 ± 0.22). SEM analysis supported quantitative findings. Conclusions: In the in vitro, three‐species biofilm model differences in material and surface roughness affected biofilm formation. In situ biofilm formation was mainly affected by the surface roughness of the specimens. Polishing of zirconia is recommended to reduce biofilm formation, while heat treatment has no significant effect.